2022
DOI: 10.3389/fped.2021.782530
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications in Paediatric Haematopoetic Cell Transplantation for Acute Lymphoblastic Leukemia: Current Status

Abstract: Haematopoietic stem cell transplantation (HSCT) in paediatric patients with acute lymphoblastic leukaemia (ALL) is associated with a variety of infectious complications which result in significant morbidity and mortality. These patients are profoundly immunocompromised, and immune reconstitution after HSCT generally occurs in astrictly defined order. During the early phase after HSCT until engraftment, patients are at risk of infections due to presence of neutropenia and mucosal damage, with Gramme-positive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 126 publications
(215 reference statements)
0
20
0
Order By: Relevance
“…There were no deaths in the global cohort and no intensive care unit (ICU) admission in the "ECIL" group, compared to two ICU admissions in the "non-ECIL" group. EAT courses for FUO episodes were significantly shorter in the ECIL group (4 [3][4][5] vs. 10 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] days; p = .002), with a mean reduction of 9 ± 3 days. Fourteen (27%) episodes of recurrent fever were observed with six documented bloodstream infections.…”
Section: Safety Of Empirical Antibiotic Therapy (Eat) Discontinuing F...mentioning
confidence: 99%
See 2 more Smart Citations
“…There were no deaths in the global cohort and no intensive care unit (ICU) admission in the "ECIL" group, compared to two ICU admissions in the "non-ECIL" group. EAT courses for FUO episodes were significantly shorter in the ECIL group (4 [3][4][5] vs. 10 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] days; p = .002), with a mean reduction of 9 ± 3 days. Fourteen (27%) episodes of recurrent fever were observed with six documented bloodstream infections.…”
Section: Safety Of Empirical Antibiotic Therapy (Eat) Discontinuing F...mentioning
confidence: 99%
“…tant for the control of a certain type of organism and are nowadays mostly understood. 3,4 Effective risk-based approaches to the prevention and early treatment of the most relevant infectious complications have been developed, including antiviral and antifungal prophylaxis, empirical antifungal and antibacterial, and pre-emptive antifungal and antiviral therapies. [5][6][7][8][9] However, despite these advances and an overall low infectious mortality in the affected patients, infectious complications in the immunocompromised host remains a dynamic and ever-evolving field that requires continuous daily attention in the form of surveillance, institution and auditing of standards of care, a high level of suspicion to new infections and new types of known infections, and interdisciplinary collaboration, discussion, and publicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of infection post HSCT can be categorized into three distinct time periods: pre-engraftment; post-engraftment, and late phase. 1,2 The highest incidence of infectious morbidity and mortality is observed in patients with granulocytopenia, especially in the pre-engraftment period. Indeed, different studies showed that 39%-60% of all BSIs occurred in the pre-engraftment period.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past five decades, allogeneic hematopoietic cell transplantation (HCT) has become a standard of care for children and adolescents with high‐risk leukemia, bone marrow failure syndromes, and several nonmalignant hematological disorders including severe immunodeficiency and certain inborn errors of metabolism 1–3 . Whereas the majority of patients will be cured, allogeneic HCT is associated with relevant and potentially life‐threatening complications in a substantial proportion of patients: Apart from leukemic relapse, graft‐versus‐host disease (GVHD), and treatment‐induced organ toxicities, treatment‐induced suppression of innate and acquired host defenses is a major driver of posttransplant morbidity and mortality, as it results in a high risk for potentially life‐threatening systemic bacterial, fungal, and viral infections 4,5 . The risk depends on the post‐HCT period and the host defenses important for the control of a certain type of organism: For invasive bacterial infections, the risk is highest during the granulocytopenic phase until engraftment, but continues at an elevated level postengraftment due to the presence of central venous catheters and increased immunosuppression and damaged tissue barriers in case of GVHD 6,7 …”
Section: Introductionmentioning
confidence: 99%